2013
DOI: 10.1155/2013/925804
|View full text |Cite
|
Sign up to set email alerts
|

Phytoagents for Cancer Management: Regulation of Nucleic Acid Oxidation, ROS, and Related Mechanisms

Abstract: Accumulation of oxidized nucleic acids causes genomic instability leading to senescence, apoptosis, and tumorigenesis. Phytoagents are known to reduce the risk of cancer development; whether such effects are through regulating the extent of nucleic acid oxidation remains unclear. Here, we outlined the role of reactive oxygen species in nucleic acid oxidation as a driving force in cancer progression. The consequential relationship between genome instability and cancer progression highlights the importance of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 180 publications
(198 reference statements)
0
47
0
2
Order By: Relevance
“…The radicals can directly react with DNA, or may indirectly act as signaling molecules to mediate DNA damage. Due to its low redox potential, guanine is the primary target of oxidation in DNA, which is a well-characterized marker for oxidative stress-induced DNA damage (Lee et al, 2013). We observed that increased 8-oxoG levels in the DNA of Sf9 cells after exposure to spinosad, and accompanied by upregulation of OGG1 and MTH1 expression (Figure 2).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The radicals can directly react with DNA, or may indirectly act as signaling molecules to mediate DNA damage. Due to its low redox potential, guanine is the primary target of oxidation in DNA, which is a well-characterized marker for oxidative stress-induced DNA damage (Lee et al, 2013). We observed that increased 8-oxoG levels in the DNA of Sf9 cells after exposure to spinosad, and accompanied by upregulation of OGG1 and MTH1 expression (Figure 2).…”
Section: Discussionmentioning
confidence: 82%
“…Under conditions of oxidative stress, ROS altered the chemical properties of biomolecules, which causes oxidative insults such as proteins denaturation, lipids peroxidation and nucleic acids' oxidation (Lee, Huang, & Shyur, 2013). Cells present a variety of defense mechanisms to neutralize the oxidative damage; antioxidant enzymes SOD and CAT constitute the first line of defense against the toxic effects of superoxide radicals (Zhang, Wang, Sun, Fang, & Tang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that following treatment with solanine, the reduced cell growth observed may be due to enhanced cellular apoptosis. (26)(27)(28). The mitochondria of a eukaryotic cell are the main site for the production of ROS, and a large amount of ROS may be produced in the process of oxidative phosphorylation.…”
Section: Solanine Significantly Inhibits the Growth Of Hepg2 Cells Anmentioning
confidence: 99%
“…The conformer with the lowest electronic energy was used for calculation. The haemolytic BDE values were calculated by the following relationship, using the standard-state enthalpies at 1 atm and 298.15K: BDE = H radical + H H − H molecule (1) where H radical is the total enthalpy of the free radical, H H is the gas-phase total enthalpy of the hydrogen atom, and H molecule is the total enthalpy of the parent molecule.…”
Section: Computational Studiesmentioning
confidence: 99%
“…radicals are commonly found in foods, drugs, and living systems. These ROS and free radicals may oxidise nucleic acids [1], denature proteins [2], and initiate the peroxidation of lipids [3] and the onset of degenerative diseases [4]. ROS are known to be the main cause of the aging process by their oxidation of cells and tissues [5].…”
Section: Introductionmentioning
confidence: 99%